2019
DOI: 10.1007/s00220-019-03548-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational Recursion Operators for Integrable Differential–Difference Equations

Abstract: In this paper we introduce preHamiltonian pairs of difference operators and study their connections with Nijenhuis operators and the existence of weakly non-local inverse recursion operators for differential-difference equations. We begin with a rigorous setup of the problem in terms of the skew field Q of rational (pseudo-difference) operators over a difference field F with a zero characteristic subfield of constants k ⊂ F and the principal ideal ring M n (Q) of matrix rational (pseudo-difference) operators. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 48 publications
(137 reference statements)
1
53
0
Order By: Relevance
“…This justifies the necessity to develop a rigorous theory of rational Hamiltonian and recursion operators. In our paper [2] we have extended the results obtained in the differential setting [3] to the difference case. In particular, we have shown that rational recursion operators generating the symmetries of an integrable differential-difference equation must be factorisable as a ratio of two compatible preHamiltonian difference operators.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This justifies the necessity to develop a rigorous theory of rational Hamiltonian and recursion operators. In our paper [2] we have extended the results obtained in the differential setting [3] to the difference case. In particular, we have shown that rational recursion operators generating the symmetries of an integrable differential-difference equation must be factorisable as a ratio of two compatible preHamiltonian difference operators.…”
Section: Introductionmentioning
confidence: 82%
“…The pair of difference operator A and B generates the hierarchy of symmetries of the modified Volterra chain. We have shown in [2] that the difference operators A and B must then form a preHamiltonian pair, that is, any linear combination C = A + λB, λ ∈ k satisfies…”
Section: Introductionmentioning
confidence: 99%
“…In this section we revise the formal calculus of variations in the differencedifferential setting as originally laid out by Kupershmidt [12], according to the more modern exposition of [6]. Moreover, we extend the so-called θ formalism to the (difference) local multivector fields.…”
Section: Functional Variational Calculus and Deformations In The Diffmentioning
confidence: 99%
“…It is well known (see, for instance, [6]) that the Volterra chain is an integrable equation admitting a biHamiltonian formulation. Indeed, one can write (4.2) with respect to two compatible Hamiltonian operators…”
Section: Constant Compatible Hamiltonian Operatorsmentioning
confidence: 99%
See 1 more Smart Citation